2019
DOI: 10.1016/j.optom.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative insufficiency in a student population in Iran

Abstract: The prevalence of AI in the present study is lower than the most prevalence rates reported in previous studies. In the present study, gender and AI showed a strong association, such that AI prevalence was significantly higher in females than males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Among college students, the prevalence of AI was reported to be 4.07% and 4.5% in Iran and South Africa, respectively. 18 , 19 A school children-based study in southern India reported a low prevalence of 0.2% 8 and this study questioned the validity of accommodation amplitude norms adopted for difference ethnicities. A study in 2019 estimated the prevalence to be in the magnitude of 6.8% among school children in Portugal.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…Among college students, the prevalence of AI was reported to be 4.07% and 4.5% in Iran and South Africa, respectively. 18 , 19 A school children-based study in southern India reported a low prevalence of 0.2% 8 and this study questioned the validity of accommodation amplitude norms adopted for difference ethnicities. A study in 2019 estimated the prevalence to be in the magnitude of 6.8% among school children in Portugal.…”
Section: Methodsmentioning
confidence: 83%
“… 22 Similarly, children with Down syndrome are found to have poorer accommodative amplitudes for their age, resulting in a high prevalence of AI ranging between 55% and 76%. 18 , 23 - 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was repeated thrice and the average measurement was noted. The accommodative amplitude in centimeters was then converted to amplitude of accommodation in diopters by dividing it by 100 [ 32 ]. The procedure was done both monocularly and binocularly.…”
Section: Methodsmentioning
confidence: 99%
“…21 years old, i.e., the critical period (8). Students form a remarkable proportion of the young population (about 4 million) (9). There are inconsistent statistical reports on the prevalence of addiction among students; however, its prevalence rate is estimated to be 2% -10% on average, including 2.6% of students from Science Ministry Universities and 1.6% of students from Medical universities (10).…”
Section: Introductionmentioning
confidence: 99%